The Ninetyeast Ridge and its Relation to the Kerguelen, Amsterdam and St. Paul Hotspots in the Indian Ocean - Nobre Silva, I; Weis, D; Scoates, J; Barling, J (Oxford University Press, 2013)
The Ninetyeast Ridge is an ∼5500 km long, north–south-oriented, submarine volcanic ridge in the eastern Indian Ocean that formed from magmatism associated with the deep-seated Kerguelen mantle plume as the Indian plate drifted rapidly northward during the Late Cretaceous. Basalts recovered along the ridge have the characteristic Dupal geochemical signature of Indian Ocean basalts, but debate concerning the nature and number of components in their mantle source persists. New multiple collector inductively coupled plasma mass spectrometry (Pb, Hf) and thermal ionization mass spectrometry (Sr, Nd) isotopic analyses were obtained for tholeiites representative of the ∼180 m of basaltic basement recovered from three drill sites (Site 758, 82 Ma; Site 757, 58 Ma; Site 756, 43 Ma) along the Ninetyeast Ridge during Ocean Drilling Program Leg 121. No systematic isotopic variation is observed along the ridge, which is inconsistent with the hypothesis of an aging mantle plume origin for the ridge. The isotopic compositions are generally intermediate between those of the volcanic products of the Kerguelen and Amsterdam–St. Paul hotspots and define mixing trends between components with relatively enriched and depleted signatures. At least three, possibly four, source components are required to explain the observed isotopic variability along the Ninetyeast Ridge. The unradiogenic signatures of some Ninetyeast Ridge basalts (e.g. 87Sr/86Sr = 0·70381–0·70438) are not related to the source of Indian MORB and indicate the presence of a relatively depleted component in a deep mantle source. A similar source component is also identified in other Indian Ocean island basalts (e.g. Crozet, Réunion) not related to magmatic activity of the Kerguelen hotspot. The Pb–Hf–Sr–Nd isotopic compositions of the Ninetyeast Ridge basalts are consistent with the presence of a mixture of recycled sediments and lower continental crust together with altered oceanic crust in their mantle source, hence supporting a deep origin for the enriched Dupal signature encountered in ocean island basalts.